apply the properties of integer exponents to generate equivalent expressions to 3^7 x 3^-9

with only positive exponents then solve the expression the answer has to a simplified fraction with no remaining exponents

I apologize for the incorrect response. Let's start again.

To generate equivalent expressions with only positive exponents for 3^7 x 3^-9, we can use the property of multiplying exponents with the same base, which states that a^m x a^n = a^(m+n).

So, applying this property, we have:

3^7 x 3^-9 = 3^(7 + (-9))

To simplify further, we can add the exponents:

3^(7 + (-9)) = 3^-2

Now, let's apply the property of a^(-n) = 1/a^n:

3^-2 = 1/3^2

Simplifying 1/3^2, we have:

1/3^2 = 1/9

Therefore, the equivalent expression to 3^7 x 3^-9 with only positive exponents is 1/9, which is already in simplified fraction form with no remaining exponents.

To generate equivalent expressions with only positive exponents, you can apply the property of integer exponents which states that a^(-n) is equal to 1/a^n.

So, applying this property to 3^-9, we can rewrite it as 1/(3^9).

Now, we can rewrite the expression 3^7 x 3^-9 using the equivalent expression.

3^7 x 3^-9 = 3^7 x (1/(3^9))

Next, we can apply the property of multiplying exponents with the same base, which states that a^m x a^n = a^(m+n).

Therefore, 3^7 x (1/(3^9)) = 3^(7 + 9)

Simplifying further,

3^(7 + 9) = 3^16

Now, to solve the expression into a simplified fraction with no remaining exponents, we can express 3^16 as a fraction.

Since the base is 3, we can write it as 3^16/1.

Thus, the simplified fraction form of 3^7 x 3^-9 is 3^16/1.

wrong

To generate equivalent expressions with only positive exponents, we can use the properties of integer exponents:

1. Product Rule: a^m * a^n = a^(m + n)
2. Quotient Rule: a^m / a^n = a^(m - n)
3. Zero Exponent Rule: a^0 = 1

Let's apply these rules step-by-step to 3^7 * 3^(-9):

Step 1: Use the Product Rule to combine the exponents of the same base, 3.
3^7 * 3^(-9) = 3^(7 + (-9))

Step 2: Simplify the exponent by adding (-9) to 7.
3^(-2)

Now, we have an equivalent expression with only a positive exponent, 3^(-2).

To solve this expression and obtain a simplified fraction, we can use the definition of a negative exponent, which states that a^(-n) = 1 / a^n.

So, 3^(-2) = 1 / 3^2

Squaring 3, we get:
3^2 = 9

Therefore, the simplified fraction for the expression 3^7 * 3^(-9) is 1/9.

To apply the properties of integer exponents to generate equivalent expressions for 3^7 x 3^-9, we can use the rule that states:

For any positive integer a and integers m and n, where m ≥ n, a^m/a^n = a^(m-n).

Step 1: Rewrite 3^-9 as 1/3^9.

We can apply this rule by subtracting the exponents:

3^7 x 1/3^9

Step 2: Combine the product of 3^7 and 1/3^9.

Using the rule that a^m x a^n = a^(m+n), we can combine the terms:

3^7 x 1/3^9 = 3^(7+(-9)) = 3^-2.

Step 3: Simplify the expression with no negative exponent.

Since we want to express the answer with only positive exponents, we can rewrite 3^-2 as 1/3^2.

3^-2 = 1/3^2.

Step 4: Evaluate the expression.

Substituting the value into the expression:

1/3^2 = 1/9.

Therefore, the result of 3^7 x 3^-9, with only positive exponents and as a simplified fraction, is 1/9.